Fusion of Tea Infusion and Bakhar (Starter of Ethnic Liquor Haria) to Develop “Tea Haria”: A Novel Approach to Ferment Tea with Insight into in Vitro Biochemical Attributes and Metabolomics - Majumder, Soumya; Saha, Sumedha; Ghosh, Arindam; Chakraborty, Sourav; Acharyya, Sukanya; Sarkar, Sahadeb; Bhattacharya, Malay (Journal of Food Technology Research, 2022)
Haria, the traditional rice based liquor of eastern India and Nepal, is an indigenous alcoholic beverage prepared by different ethnic communities where bakhar is used as starter culture which is a tablet like mixed culture of various yeasts, filamentous molds, and lactic acid bacteria etc. This research work was designed to make a fusion of tea infusion and bakhar to produce “Tea Haria”. Tea infusion and bakhar were co-cultured for fermentation which was further characterized by different physicochemical and biochemical parameters. In vitro assessment of antioxidant, antidiabetic, anti-ipid peroxidation activity and antibacterial activity were assessed. Primary investigations for qualitative characters on this fermented broth or tea haria revealed the presence of steroids, tannin, flavonoids, phenol, cardiac glycosides, coumarin, caffeine etc. Tea haria, the fermented broth showed high free radical scavenging activity. The antioxidant activity, acidity and alcohol percentage were seen to be gradually increased while brix and specific gravity of broth were decreased during the first fifteen days of fermentation. Gas chromatography-mass spectrometry analysis revealed the presence of thirty-three compounds including many potential antioxidant molecules and other bioactive agents which validated the qualities detected and estimated through in vitro assays in tea haria. Presence of alcohol with medicinally active compounds and antioxidant, antibacterial and other biological activities have made this tea haria a bioactive probiotic-fermented formulation and, furthermore, brought out the ethnic knowledge of haria fermentation, specifically, ethnic starter bakhar as a useful biotechnological tool which can be utilized in research and development of fermentation technology.